CATALASE ACTIVITY IN LEPTOSPIRA - Rao, P. J. (1964)
Rao, P. J. (University of Illinois, Urbana), A. D. Larson, and C. D. Cox. Catalase activity in Leptospira. J. Bacteriol. 88:1045–1048. 1964.—A number of serotypes of Leptospira were found to possess catalase activity, although considerable variation in activity existed among various serotypes. Catalase activity of L. pomona was reduced by inhibitors commonly employed for arresting catalase activity in other biological systems. Catalase activity was increased three to five times by growing cultures under conditions of oxygen availability; however, aeration had no beneficial effect on total viable cell crop. The relationship of oxygen to metabolism and future studies on virulence of the leptospirae is discussed.